2005
DOI: 10.1121/1.1853934
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of structural response and fatigue endurance of aircraft flap-like box structures subjected to acoustic loading

Abstract: The results of an extensive test program to characterize the behavior of typical aircraft structures under acoustic loading and to establish their fatigue endurance are presented. The structures tested were the three flap-like box-type of structures. Each structure consisted of one flat (bottom) and one curved (top) stiffener stiffened skin panel, front, and rear spars, and ribs that divided the structures into three bays. The three structures, constructed from three different materials (aircraft standard alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Under high cyclic loads or corrosive environment, fatigue cracks may initiate from the rivet holes and go span-wise along the stiffeners or spars. Xiao et al [19] reported their study on the fatigue endurance of three aircraft flap-like box structures made of various materials (aluminium alloy, CFRP and GLARE) under acoustic loading. NDT examinations are still needed to characterize those defects.…”
Section: Introductionmentioning
confidence: 99%
“…Under high cyclic loads or corrosive environment, fatigue cracks may initiate from the rivet holes and go span-wise along the stiffeners or spars. Xiao et al [19] reported their study on the fatigue endurance of three aircraft flap-like box structures made of various materials (aluminium alloy, CFRP and GLARE) under acoustic loading. NDT examinations are still needed to characterize those defects.…”
Section: Introductionmentioning
confidence: 99%
“…Ustilovsky and Arone tested multi‐crack panel‐type aluminium specimens under constant amplitude loading, constant amplitude with superimposed overloads and random variable amplitude load history. Xiao et al presented an extensive test programme to characterize the behaviour of typical aircraft structures under random acoustic loading and to establish their fatigue endurance. The structures tested were the three flap‐like box‐type structures.…”
Section: Introductionmentioning
confidence: 99%